RAE1ε ligand expressed on pancreatic islets recruits NKG2D receptor-expressing cytotoxic T cells independent of T cell receptor recognition - Markiewicz, Mary A. (2012)
The mechanisms by which cytotoxic T lymphocytes (CTLs) enter and are retained in non-lymphoid tissue are not well-characterized. Using a transgenic mouse expressing the NKG2D ligand retinoic acid early transcript 1ε (RAE1ε) in β-islet cells of the pancreas, we found RAE1 expression was sufficient to induce the recruitment of adoptively transferred CTLs to islets. This was dependent on NKG2D expression by the CTLs and independent of antigen recognition. Surprisingly, the recruitment of CTLs resulted in the subsequent recruitment of a large number of endogenous lymphocytes. Whereas transgenic mice did not develop diabetes, RAE1 expression was sufficient to induce insulitis in older, unmanipulated transgenic mice that was enhanced by viral infection and pancreatic inflammation. These results demonstrate that the expression of an NKG2D ligand in islets is sufficient to recruit CTLs regardless of their antigen-specificity and induce insulitis.